ACP: statistical yearbook. ACP: annuaire statistique. - Statistical Office of the European Communities ([Luxembourg, Statistical Office of the European Communities], 1976)
Selected main demographic, economic and social indicators of those countries signatory to the Lomé Convention (called the ACP countries)
English and French.
SERBIB/SERLOC merged record
Keywords: European Economic Community -- Africa -- Statistics -- Periodicals; Africa -- Statistics -- Periodicals